PEMBINAAN PEMANFAATAN MEDIA VIDEO EDUKASI SEBAGAI STRATEGI PEMBELAJARAN INTERAKTIF DI PONDOK PESANTREN DARUL ULUM PADANG - Alfajri Alfajri; Martin Kustati; Gusmirawati Gusmirawati (Jurnal Manajemen Pendidikan, 2026)
This study aims to improve the quality of learning at the Darul Ulum Padang Islamic Boarding School through fostering the use of educational video media as an interactive learning strategy. This research is motivated by the dominance of conventional learning methods, such as lectures and bandongan, which result in low student engagement in the learning process. This study used a Participatory Action Research (PAR) approach involving 5 ustadz and 15 students as participants. The activity was carried out for three months through three main stages, namely preparation, implementation, and evaluation-reflection. Data collection techniques included participatory observation, semi-structured interviews, and documentation. The results showed that the use of educational video media was able to increase student engagement in learning. Active questioning increased from 15% to 55%, involvement in discussions increased from 20% to 70%, and learning focus increased from 55% to 80%. In addition, the level of understanding of students in the high category increased from 20% to 60%. The coaching carried out also improved the competence of the ustadz in integrating digital media into learning without eliminating the characteristics of Islamic boarding school education based on the yellow books. Thus, educational video media has proven effective as an interactive learning strategy that supports the transformation of Islamic boarding school education in the digital era.